Analisis Modal Kerja Dan Pengaruhnya Terhadap Pertumbuhan Perusahaan - Muktiadji, Nusa; Sastra, Heri (Jurnal Ilmiah Manajemen Kesatuan, 2013)
Working capital is one of important factors in a company. It’s current asset which easy to be cashed and utilized for daily operational activities of the company. The amount of reasonable working capital in a company is the amount of working capital which is enough or in mutual accord with the fund needed to finance the operational activities. The purpose of this research is to find out the correlation and impact of working capital on the company’s growth. The analysis is done to know whether the amount of working capital has correlation and impact towards the company’s growth. The research was conducted at PT. Indocement Tunggal Prakarsa, Tbk, the national companies running in cement. The result of the research shows that PT. Indocement Tunggal Prakarsa, Tbk has been efficient in managing their working capital. It’s proven by the more increase of working capital of the the companies. PT. Indocement Tunggal Prakarsa, Tbk has been able to make profit with the result that there is growth in the company. Yet, at PT. Indocement Tunggal Prakarsa, Tbk, the profit yielded cannot make the growth increases. Keywords : Working capital; growth.